INTERNALISASI NILAI KARAKTER HINDU DALAM AJARAN PRADNYAN DAN PURUSOTTAMA - Anak Agung Gde Krisna Paramita; Dewa Nyoman Arsana; Dewa Ayu Kade Linda Dewi (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
This study examines a concept in the internalization of Hindu character values contained in the teachings of Pradnyan and Purusottama, as the main object, namely Hindu Man whose character is according to the concepts of Pradnyan and Purusottama teachings. This research uses qualitative data-based methods in the form of narrative text studies. The description of this study is the character values in the teachings of Pradnyan and Purusottama in the book Sarasamuccaya sloka (304-306), namely the character of Hindu humans:  1. Tan girang yan inalem, 2. Tan alara yan inida, 3. Tan kataman krodha, 4. Tan kataakenang sawacana, 5. Lasting dhiraning manah, 6. Taranggenangen dosaning len, 7. Tan saidakenang parapawada, 8. Guna rahayu kenget nira, 9. Apageh ri maryadanira, this concept is Nawa Purusottama, namely the nine main human traits in the Hindu concept that must be owned and implemented in social religious life.